Retrofuturismo? - Rossi Prodi, Fabrizio (Firenze Architettura, 2019)
With curiosity due to its karstic reemergence, and some perplexity, this article explores Retrofuturism, an art movement – not mainly architectural – that investigates the influence of future representations produced in past eras, expressing a nostalgia for the memory of those anticipations, balanced between past and future, alienation and the promises of redemption offered by new technologies.